Stentolith in Bile Duct: A Neglected Entity—Case Report with Review of Literature - Gupta, Amit; Rajput, Deepak; Chennat, Jaine John; Singla, Tanuj; Ahmed, Shaik Sameer (The Surgery Journal, 2022)
Stentolith is a forgotten stent that acts as a nidus for stone formation leading to a stone-stent complex. Once the planned procedure is completed, these stents should be removed within 4 to 6 weeks, but if they are required for a longer period, then they should be replaced every 3 to 6 months. Devastating complications may ensue —such as cholangitis, biliary stricture, or secondary biliary cirrhosis. Management primarily comprises surgical intervention with common bile duct exploration or endoscopic clearance. The majority of patients eventually develop symptoms that lead to their diagnosis and subsequent management. This article, however, details the case of a silent stentolith and how it may have led to disastrous complications if surgical intervention was not done promptly.
Keywords: stentolith; cholelithiasis; stenting; cholangiography